2006
DOI: 10.1080/00288330.2006.9517447
|View full text |Cite
|
Sign up to set email alerts
|

Survey of cyanotoxins in New Zealand water bodies between 2001 and 2004

Abstract: Contamination of drinking and recreational water bodies by toxic cyanobacteria is a significant water management issue in many countries. Until recently, knowledge of the occurrence of cyanotoxins and species responsible for cyanotoxin production in New Zealand was limited. In this study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 32 publications
5
51
1
Order By: Relevance
“…This 50% value agrees well with estimates from culture collections; nearly half the cyanobacteria in the Pasteur Culture collection and the NWA collection were estimated to have the potential for microcystin production (Bell et al 1998, unpubl. ), and results were similar in a survey of New Zealand water bodies (Wood et al 2006). Low levels of toxicity were found equally in large and small lakes; 40% of the samples collected from all three basins in Lake Erie had measurable levels of particulate microcystin, though the majority of those samples were concentrated in the more eutrophic western basin.…”
Section: Occurrence Of Cyanobacteria Toxins In New York State Waterssupporting
confidence: 63%
See 1 more Smart Citation
“…This 50% value agrees well with estimates from culture collections; nearly half the cyanobacteria in the Pasteur Culture collection and the NWA collection were estimated to have the potential for microcystin production (Bell et al 1998, unpubl. ), and results were similar in a survey of New Zealand water bodies (Wood et al 2006). Low levels of toxicity were found equally in large and small lakes; 40% of the samples collected from all three basins in Lake Erie had measurable levels of particulate microcystin, though the majority of those samples were concentrated in the more eutrophic western basin.…”
Section: Occurrence Of Cyanobacteria Toxins In New York State Waterssupporting
confidence: 63%
“…Not all cyanobacterial toxins pose an equal risk to lakes and reservoirs. As has been observed in other systems (Wood et al 2006), microcystin toxins were the most important, both in terms of their maximum concentrations and in terms of their widespread abundance. They are also produced by a large number of different genera and species other than Microcystis aeruginosa, complicating the use of microscopic techniques for assessing the risk they pose to a water body.…”
Section: Discussionmentioning
confidence: 67%
“…Substitution of hAr for Arg was also relatively common in MCs from a Finnish Nostoc sp. The [D-Ala 1 ] in MCs is generally highly conserved, although substitutions by serine or leucine in Several studies have demonstrated variability in MC concentrations when different detection methods were used (6,28,52). The ADDA-ELISAs used during the present study measure the total amount of ADDA-containing compounds in the sample, with the second ELISA having lower cross-reactivity with free ADDA and nodularin (Lyn Briggs, personal communication).…”
Section: Physical and Chemical Characteristics Of Pondsmentioning
confidence: 99%
“…These blooms are aesthetically unpleasant and can have detrimental effects on aquatic ecosystems through altering trophic structure and functionality (Havens 2008), and by decreasing water quality (Robarts et al 2005). Additionally, many of the species responsible for these blooms produce natural toxins, known as cyanotoxins (Wood et al 2006). These toxins are a threat to humans and animals if consumed in drinking water or contacted during recreational activities.…”
Section: Freshwater Cyanobacteria and Algaementioning
confidence: 99%
“…In multiple lakes and rivers across New Zealand, cyanobacteria (blue-green algae) form planktonic or benthic blooms (Wood et al 2006. These blooms are aesthetically unpleasant and can have detrimental effects on aquatic ecosystems through altering trophic structure and functionality (Havens 2008), and by decreasing water quality (Robarts et al 2005).…”
Section: Freshwater Cyanobacteria and Algaementioning
confidence: 99%